1983
DOI: 10.1176/appi.psychotherapy.1983.37.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Family Constellation in India

Abstract: The article first outlines historical suicide patterns. Case histories mirror a wide range of frustrations and family tensions in our present generation and show the socioeconomic, sociophilosophical, and cultural changes that are sweeping Indian society and are greatly adding to the tensions in life, resulting in a substantially higher occurrence of suicide. Varieties of family patterns are described that predispose an individual to suicidal behavior. It has been stressed that the single most important variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…The overall incidence of suicide by self-immolation found in this study is in general agreement with the findings of other studies reported from other countries (Sheth et al 1994;Gehlot and Nathawat 1983;Singh et al 1982;O'Donoghue et al 1998;Ho and Ying 2001;McDonald 2004;BBC Monitoring South Asia 2004;Mzezewa et al 2000;Laoe and Ganesan 2002;Palmu et al 2004;Nakae et al 2003). Similar to research reports from other provinces in the country (Rastegar and Alaghebandan 2004;Zarghami and Khalilian 2002;Groohi et al 2002;Dibaei and Gharebagi 2000;Esfandiari 2001;Ganizadeh et al 1996), there was an increasing trend of self-immolation over time in the northeast region.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall incidence of suicide by self-immolation found in this study is in general agreement with the findings of other studies reported from other countries (Sheth et al 1994;Gehlot and Nathawat 1983;Singh et al 1982;O'Donoghue et al 1998;Ho and Ying 2001;McDonald 2004;BBC Monitoring South Asia 2004;Mzezewa et al 2000;Laoe and Ganesan 2002;Palmu et al 2004;Nakae et al 2003). Similar to research reports from other provinces in the country (Rastegar and Alaghebandan 2004;Zarghami and Khalilian 2002;Groohi et al 2002;Dibaei and Gharebagi 2000;Esfandiari 2001;Ganizadeh et al 1996), there was an increasing trend of self-immolation over time in the northeast region.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the wide range of published research on the occurrence and epidemiological features of suicide by self-immolation (Cave Bondi et al 2001;Rastegar Lari and Alaghebandan 2004;Sheth et al 1994;Gehlot and Nathawat 1983;Singh et al 1982;Zarghami and Khalilian 2002;Hamshahri Newspaper 2000;Açikel et al 2001;Groohi et al 2002;Dibaei and Gharebagi 2000;Rothschild et al 2001;O'Donoghue et al 1998;Ho and Ying 2001;McDonald 2004;Iran Newspaper 2004;BBC Monitoring South Asia 2004;Mabrouk et al 1999;Mzezewa et al 2000;Laoe and Ganesan 2002;Wagle et al 1999;Kumar 2003;Esfandiari 2001;Cameron et al 1997;Krummen et al 1998;Ganizadeh et al 1996;Palmu et al 2004;Nakae et al 2003;Haberal et al 1989), few published data are available on the survival patterns, prognosis, and predictor factors of this type of suicide.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[7] This over representation could also be due to the disintegration of joint family system within the society which has led to change in family environment and added burden on the family members. [21]…”
Section: Discussionmentioning
confidence: 99%
“…[33] Attempts by persons from extended families were mostly attributed to mental illness and stress in contrast to those from nuclear families. This suggests that factors specific to nuclear families might be involved in many attempts, which would need further study.…”
Section: Discussionmentioning
confidence: 99%